Hardware/software co-design of a GPS receiver - Han, Junyuan. (2009)
The Global Positioning System (GPS) is heavily used in today’s modern world. Many civilian and military operations are relying on GPS to operate effectively. Many development projects have been undertaken to fully utilize this technology. Field Programmable Gate Array or FPGA for short is used for a range of applications and development. This is due to the reconfigurable nature of the FPGA which can be easily reconfigured to match any requirements in the applications required. The objective of this project is to use the recorded digitized GPS signal to work out the receiver’s location. Various methods of integrating of the correlator module in the Celoxica RC10 FPGA and the navigation module in the Xilinx University Program Virtex-II Pro Development Board were also carried out. The design and implementation of the FPGA GPS Receiver will be discussed together with some of the problems encountered while integrating the FPGAs. Throughout this period of time, the author has gained valuable insight and experience in designing the embedded systems. Various software were learnt and used in the process to meet the objectives of the project.